External and intestinal parasites of the austral thrush turdus falcklandii (Aves, turdidae) in central Chile Parasitas externos e intestinais do tordo-austral Turdus falcklandii (Aves, Podicipedidae) no Chile - Llanos Soto, Sebastián (2019)
A total of thirty Austral thrushes Turdus falcklandii Quoy & Gaimard, 1824 (Turdidae) carcasses were brought to the Departamento de Ciencia Animal, Facultad de Ciencias Veterinarias, Universidad de Concepción, to be examined for ecto- and endoparasites. Ectoparasites were found on 20% (6/30) of the thrushes and belonged to species Brueelia magellanica Cichino, 1986 (Phthiraptera), Menacanthus eurysternus Burmeister, 1838 (Phthiraptera) and Tyrannidectes falcklandicus Mironov & González-Acuña, 2011 (Acari). Endoparasites were isolated from 26.6% (8/30) of the birds and identified as Lueheia inscripta Westrumb, 1821 (Acanthocephala), Plagiorhynchus cylindraceus Goeze, 1782 (Acanthocephala), Wardium sp. sensu Mayhew, 1925 (Cestoda), Dilepis undula (Cestoda) Schrank, 1788, and Zonorchis sp. (sensu Travassos, 1944) (Trematoda). To our knowledge, all endoparasites collected in this study are new records in T. falcklandii and expand their distributional range to Chile.